Spectroscopy, Morphology, and Electrochemistry of Electrospun Polyamic Acid Nanofibers - Hamnca, Siyabulela; Chamier, Jessica; Grant, Sheila; Glass, Timothy; Iwuoha, Emmanuel; Baker, Priscilla (Frontiers in Chemistry, 2022)
Polyamic Acid (PAA) nanofibers produced by electrospinning method were fully characterized in terms of morphology and spectroscopy. PAA nanofiber modified screen carbon printed electrode was applied to the detection of selected sulphonamides by following an electro-analytical protocol. The polyamic acid (PAA) nanofibers were characterized using Fourier Transform infrared (FTIR) spectroscopy to study integrity of polyamic acid functional groups as nanofibers by comparing them to chemically synthesized polyamic acid. Scanning electron microscope (SEM) was used to confirm the morphology of the produced nanofibers as well as 3D arrangement at the electrode interface. Brunauer-Emmett-Teller (BET) was used to determine the surface area of the nanofibers. Atomic force microscopy (AFM) used to study the porosity and surface roughness of the nanofibers. Electrochemical evaluation based on diffusion-controlled kinetics was applied to determine the number of electrons transferred in the system, the surface concentration of the deposited PAA thin film (2.14x10-6 mol/cm2) and the diffusion coefficient (De) for the PAA nanofiber modified screen-printed carbon electrode (9.43x10-7 cm-2/s). The reported LODs for sulfadiazine and sulfamethazine detection are consistent with requirements for trace level monitoring by early warning diagnostic systems.